Trend Analysis Using Bibliometric Study on Digital Literacy in Education - Arissaputra, Rivaldi; Sobandi, Ade; Sentika, Sarah; Adib Sultan, Mokh; Putu Nurwita Pratami Wijaya, Ni (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Digital literacy has emerged as a critical skillset in response to the rapid evolution of digital technology. The COVID-19 pandemic has notably accentuated its significance, particularly in educational settings. In this study, a bibliometric analysis using VoS Viewer was conducted on 725 articles retrieved from the Google Scholar database, covering the period from 2013 to 2023. Employing qualitative methods, this research aims to comprehensively analyze the research trends in Digital Literacy in Education, focusing specifically on its practical applications and outcomes. The findings of the study provide multifaceted insights into the use of digital literacy in education. Through cluster analysis, prominent themes and interrelationships within the field have been identified and interpreted. Notably, the results shed light on the actual implementation and observed outcomes of digital literacy initiatives in educational contexts. The analysis discerns the practical implications and tangible effects of digital literacy on learning outcomes, pedagogical strategies, and student engagement. This study emphasizes the need for a nuanced approach to digital literacy, moving beyond mere technical competence. It underlines the importance of integrating responsible use, critical thinking, and digital citizenship within educational curricula and pedagogical practices. The research findings assert the necessity of aligning digital literacy initiatives with evolving educational needs to equip students with essential skills for navigating the digital landscape effectively. The implications of this study extend to policymakers, educators, and researchers involved in digital literacy initiatives. Highlighting the actual utilization and impact of digital literacy in education, the study urges stakeholders to refine educational practices and policies. Furthermore, it underscores the significance of continuous integration and adaptation of digital literacy within educational frameworks, aiming to harness its potential for enriching learning experiences and preparing students for the demands of the digital age. This research contributes to an in-depth understanding of the practical application of digital literacy in educational settings. It accentuates the pressing need to observe, assess, and adapt digital literacy initiatives to foster comprehensive learning outcomes.